Some Considerations on the Underlying Need to Reform the Current International Monetary System (Global Journal of Management and Business Research, 2014)
This paper addresses a pressing current topic on the International Monetary System (IMS) and the need for its fundamental reform. In principle, at present, this need for reform is agreed by all specialists and more and more of those who govern the world's countries. The paper presents the main vulnerabilities of SMI, some aspects of his background, a review of several papers, a brief critical analysis of IMS and some proposals and conclusions which the authors deem useful. The novelty the paper brings concerns the design of a new currency of international reserve and also the proposal the for the issuance and surveillance of its use should be formed a new entity that has the role of the Central Bank but worldwide.
Keywords: international monetary system; reformation; imbalances; crisys; international reference currency